Comparative analysis of eﬃcacy and safety of various anti-tuberculosis therapy regimens in patients with MDR/XDR tuberculosis - E. P. Myshkova; T. I. Petrenko; T. A. Kolpakova (Туберкулез и болезни лёгких)
The objective: to evaluate the eﬃcacy and safety of various anti-tuberculosis therapy regimens for multiple drug resistant (MDR) and extensive drug resistant pulmonary tuberculosis in the intensive phase of treatment lasting for 8 months minimum.Subjects and Methods. A single-center cohort prospective-retrospective clinical study was conducted, which included 166 patients aged 18 to 70 years with active pulmonary tuberculosis and proven MDR of Mycobacterium tuberculosis, who received chemotherapy according to regimens IV and V. The treatment regimen of patients in Group I (n = 96) included modern anti-tuberculosis drugs (TBdrugs) – bedaquiline, linezolid, respiratory ﬂuoroquinolone (levoﬂoxacin, moxiﬂoxacin, sparﬂoxacin), cycloserine, pyrazinamide, and perchlozone at a dose of 8-10 mg/kg, 1 time per day after meals during the intensive phase of treatment, that was at least 8 months. Patients from Group II (n = 70) received a respiratory ﬂuoroquinolone (levoﬂoxacin, moxiﬂoxacin, sparﬂoxacin), aminoglycoside (amikacin), cycloserine, pyrazinamide, ethambutol, and prothionamide.Results. After 3 months of treatment, symptoms of intoxication disappeared in 22 (81.5%) patients in Group I, and only 41 (61.2%) in Group II (p = 0.04; TTF). In patients of Group I versus Group II, the body temperature returned to normal within a shorter time: 2.8 and 4.3 weeks, respectively (p < 0.05). By the end of the intensive phase of treatment (8 months), sputum conversion conﬁrmed by culture was observed more often in patients of Group I compared to Group II (85 and 80%, pχ2 = 0.003). Adverse events (AE) caused by TB drugs in Group I were observed signiﬁcantly more often versus Group II: gastroenterological adverse events (pχ2 = 0.05), cardiac adverse events (pTTP = 0.05), and endocrinological adverse events (pTTP = 0.05). Neurotoxic AEs tended to develop more often in Group I (pTTP = 0.06). Ototoxic AEs were more frequently observed in Group II where the treatment regimens included aminoglycosides (pχ2 = 0.05). To maintain adequate chemotherapy regimens IV or V over long-term treatment, MDR tuberculosis patients need continuous monitoring of AEs, intravenous administration of two or three TB drugs, and timely therapy to manage manifestations of AEs.